Конструктивні характеристики інгумаційних поховань черняхівської культури Шишацького могильника - Рейда, Р.М.; Гейко, А.В.; Сапєгін, С.В. (Археологія і давня історія України, 2019)
Стаття присвячена конструктивним характеристикам поховань-інгумацій черняхівської культури Шишацького могильника. Усього до вибірки увійшло 89 інгумаційних поховань, в яких простежено їх конструкцію. Виділено кілька типів таких поховань (поховання в прямій ямі, в прямій ямі з додатковим елементом, поховання у ямі з заплічками, катакомба) та виокремлено їх підтипи. The article deals with the characteristics of graves’ constructions of Shyshaky cemetery of Cherniakhiv culture. During the total period of excavation work for eight seasons there were found 156 burials. The graves’ structures were traced in 89 graves of Shyshaky cemetery. The inhumations were oriented to the west and to the north and the amount of them was 98.5 % of the total number. These burials were in grave pits, lerge graves, barbarian chambered graves or in grave pits with some constructive features. The ratio of inhumations was as follows: in grave pits (Fig. 1—2), lerge graves (Fig. 3), barbarian chambered graves (Fig. 4) or in grave pits with some constructive features (Fig. 2: 3; 3: 3) are given in the table (Fig. 5). The burial constructions of Shyshaky cemetery refer to late periods of Cherniakhiv culture and they are dated to the second part of the 4th — 5th centuries.